2021
DOI: 10.1111/1346-8138.15781
|View full text |Cite
|
Sign up to set email alerts
|

Normolipemic xanthomatized Sweet’s syndrome: A variant of Sweet’s syndrome with myelodysplastic syndrome

Abstract: We report a rare case of xanthomatized Sweet's syndrome with myelodysplastic syndrome (MDS) in a patient who presented with erythematous plaques on his chest that were elevated and became yellowish. A diagnosis of MDS with single lineage dysplasia was made during the development of the eruption. Bone marrow biopsy showed an increased number of megakaryoblasts. Histopathologically, there was neutrophil infiltration with leukocytoclasia and the infiltration of xanthomatous cells. Immunohistochemical analysis rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Recently, a novel subtype of SS, normolipemic xanthomized Sweet syndrome, was reported by Kamimura et al Microscopic examination of this unusual case revealed CD163-positive foam cells to accompany dense neutrophilic infiltrate extending into the deep dermis [69]. Further reports may aid in further characterization of this variant.…”
Section: Other Histologic Patternsmentioning
confidence: 73%
“…Recently, a novel subtype of SS, normolipemic xanthomized Sweet syndrome, was reported by Kamimura et al Microscopic examination of this unusual case revealed CD163-positive foam cells to accompany dense neutrophilic infiltrate extending into the deep dermis [69]. Further reports may aid in further characterization of this variant.…”
Section: Other Histologic Patternsmentioning
confidence: 73%
“…Another unusual case reported was that of a patient with Sweet syndrome characterized by normolipemic xanthoma-infiltrated neutrophilic dermatosis developed with myelodysplastic syndrome (MDS) with single-lineage dysplasia [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…A new and rare variant of SS, normolipemic xanthomized Sweet syndrome (A. Kamimura et al [ 65 ]), clearly discloses that SS classification is not near to completion, while SS pathogenesis has a few starting theories. This unique case describes a prolonged evolution with adverse outcomes, overlooking the MDS that is affiliated with a good prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…There have been other clinicopathogical variants reported in the literature in the setting of MDS/MPN mentioned above [17]. Among all of these variants, it is worth highlighting the subcutaneous Sweet syndrome (S-SS) or neutrophilic lobular panniculitis (Figure 1D-F) [18,19].…”
Section: Other Morphological Variants Of the Sweet Syndromementioning
confidence: 95%